Deregulation of mTORC1-TFEB axis in human iPSC model of GBA1-associated Parkinson’s disease - Mubariz, Fahad; Saadin, Afsoon; Lingenfelter, Nicholas; Sarkar, Chinmoy; Banerjee, Aditi; Lipinski, Marta M.; Awad, Ola (Frontiers in Neuroscience, 2023)
Mutations in the GBA1 gene are the single most frequent genetic risk factor for Parkinson’s disease (PD). Neurodegenerative changes in GBA1-associated PD have been linked to the defective lysosomal clearance of autophagic substrates and aggregate-prone proteins. To elucidate novel mechanisms contributing to proteinopathy in PD, we investigated the effect of GBA1 mutations on the transcription factor EB (TFEB), the master regulator of the autophagy-lysosomal pathway (ALP). Using PD patients’ induced-pluripotent stem cells (iPSCs), we examined TFEB activity and regulation of the ALP in dopaminergic neuronal cultures generated from iPSC lines harboring heterozygous GBA1 mutations and the CRISPR/Cas9-corrected isogenic controls. Our data showed a significant decrease in TFEB transcriptional activity and attenuated expression of many genes in the CLEAR network in GBA1 mutant neurons, but not in the isogenic gene- corrected cells. Further analysis demonstrated that GBA1-mediated lipid substrate accumulation results in increased activity of mTORC1, the main upstream negative regulator of TFEB. Increased mTORC1 activity resulted in excess TFEB phosphorylation and decreased nuclear translocation in PD neurons. Pharmacological mTOR inhibition restored TFEB activity, decreased ER stress and reduced α-synuclein accumulation, indicating improvement of neuronal protiostasis. Moreover, treatment with the lipid substrate reducing compound Genz-123346, decreased mTORC1 activity and increased TFEB expression in the mutant neurons. Our study unveils a new mechanism contributing to PD susceptibility by GBA1 mutations in which lipid imbalance mediates ALP dysfunction through deregulation of mTOR-TFEB axis. It also indicates that pharmacological restoration of TFEB activity could be a promising therapeutic approach in GBA1-associated neurodegeneration.